Challenges to Research Activities among Academic Clinicians at the International Medical School, Management and Science University, Malaysia - , Sohayla M. Attalla; , Nihal A. Hanafy; , Mahfuza Akter; , Kavitha Ashok Kumar (Archives of Current Research International, 2022)
Scientific research is the main factor for developing the societies. The qualified university staff are expected to have the biggest share in research work but unfortunately may be distracted by academic work or suffering variable factors that hinder the research activities. The objective of this study was to determine the prevalence of those interested in research and have research activities among staff at the IMS-MSU and investigate the factors that may hinder the research activities among the medical school academicians in order to put recommendations to enhance the research activities. Results showed that 90% of the working staff are interested in research, 35.2% had 1-5 publications and 12.9% had 30 publications along their working life. 51.6% of the respondents are holding master and 38.7% are holding PhD that gives indication for the qualifications of the school staff that are suitable to perform research but unfortunately those having more than > 15 researches along their work life represented 22.5% which is a small percentage but it can be accepted when it is noticed that 28% only of the working power are working since more than 10 years. 48.4%% of the working power are having 1-5 publications in the last year which mean that the research activities have been increasing in the last year when it is noticed that 35.2% of the staff are having 1-5 publications along their working life. The most challenging factor for research activities from the academicians’ perspective was the multifactorial effects (35.4%), research related factors (32.3%) followed by the organizational (19.4%) and the personal factors (12.9%). It is concluded that the research ecosystem has been developing and growing fast in the last 5 years among IMS-MSU staff, yet all the affecting challenges are encouraged to be corrected for more enhancement of research activities.